Global marketing strategies : an examination of the Malaysian wooden furniture industry / Jamil Bojei, Mohd. Shahwahid Haji Othman and Yeap Teik Bu - Bojei, Jamil; Othman, Mohd. Shahwahid; Yeap, Teik Bu (Faculty of Business and Management ; UiTM Press, 2002)
The Malaysian wooden furniture industry's export performance has shown a remarkable I achievement over the last decades. This industry like other natural evolving clusters is characterized by small-and-medium-scale industries (SMIs), labor intensive and less specialized production technology. The turning point of the industry began with the launching of the First Industrial Master Plan (1986-1995), whereby the government provided consistent and user-friendly policy measures to allow healthy competition among the manufacturers and entrepreneurship development. The influx of foreign direct investments spurred the technology transfer in the furniture industry by introducing the private subcontracting system [Original Equipment Manufacturing (OEM)], to local entrepreneurs. The resource advantage and cheap unskilled labour allowed local entrepreneurs to have sufficient time to nurture and to penetrate new overseas markets. The objective of the study is to examine the factors leading to different global marketing strategies adopted in the wooden furniture industry by Malaysian entrepreneurs. The hypothesis suggests that size of the firm, the firm's experiences in exporting, the decision maker *s attitude, current global marketing strategy and the firms establishment can affect the firm's choice in global marketing strategy. The findings show that firm's characteristics and the decision maker's attitude towards exports are significant determinants of a firm's success in the export arena.